Introduction to types of motorized vehicles based on shape and model using convolutional neural network based on digital images - Hurairah, Wahu Abi; Mmurtopo, Aang Alim; Fadilah, Nurul (Journal of Intelligent Decision Support System (IDSS), 2024)
The process of classifying images of different vehicles is an interestingchallenge for research. The process of classifying different vehiclesis widely used in various things such as electronic ticketing, e-parking andother fields. One method often used in the classification process is the Convolutional Neural Network (CNN) method. The CNN method is widely used toperform the classification process because it has been tested and proven to beeffective in image processing and pattern recognition. By classifying differentvehicles, CNN can automatically extract features from image data and detect complexpatterns. The CNN method provides high efficiency and accuracy in classifyingvarious vehicles for various practical applications such astraffic management and license plate recognition systems. The studyperformed motor vehicle image recognition by determiningthe types of two-wheeled vehicles (motorcycles) and 4-wheeled vehicles (cars) using a combination of Otsu threshold and CNN method. From the results of the research, two types of vehicles can be well identified, showing the confidence level of the classification process. of.).